Fenomena Maraknya Kasus Pencemaran Nama Baik dalam Bermedia Sosial dalam Masyarakat Ditinjau dari UU ITE - Andi Humaira Mahira; Vania Oktaviani Dewi; Feby Welgaputri; Nabila Zalfa; Karina Josephine Siregar; Kayla Tiara Reynita; Mulyadi Mulyadi (Madani: Jurnal Ilmiah Multidisiplin, 2023)
In Indonesia, the social, political, cultural, and other aspects of his life are governed by law. Article 1 paragraph 3Â  of the 1945 Constitution of the Republic of Indonesia makes it clear that Indonesia is a constitutional state. The development and advancement of technology play a significant role in increasing cases of pollution of good name in the current era. There are social media apps like Twitter, Instagram, and TikTok that are easily accessible by users around the world. In this case, the occurrence of good-name contamination is very vulnerable because everyone can easily and freely manage their own accounts. As for the formula of the problem, the first is the regulation of pollution of good names according to the positive law in Indonesia, and the second is the attempt to resolve the case of pollution of good names in Indonesia. This research includes a type of yuridic research, which refers to the applicable legal regulations and uses research methods through library studies. The results of the research found that the pollution of the good name was regulated in the special Chapter of the KUHP entitled Disgrace and the ITE Law, as well as that efforts to resolve the case of good name contamination were carried out after there was a complaint from the public that there had been a criminal offence of the corruption of a good name and then continued with repressive efforts.